Avian embryology - Bronner-Fraser, Marianne (Methods in cell biology, 2008)
This revised edition will continue to serve as the most complete and up-to-date guide to the use of the avian embryo in studies of vertebrate development. It will include new approaches to analysis of the chick genome, gene knock-out studies using RNA interference, morpholinos, and other cutting edge techniques. As with the original edition, emphasis has been placed on providing practical guidance, highlighting potentials and pitfalls of all key cell biological and embryological techniques. * Fully revised second edition, organized into basic and advanced methods. * New chapters with modern techniques only in use in the past decade, with an emphasis placed on providing practical guidance - highlighting potentials and pitfalls. * International team of contributors with broad expertise in using the avian embryo to study vertebrate development. * Includes new approaches including analysis of the chick genome, gene knock-out studies using RNAi, morpholinos, and other cutting edge techniques.